The Influence Of Competitive Strategy On Corporation Performance - Leny Suzan; Hilda Revi O. (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2021)
In order to support the ability of business people to face all the challenges of increasingly fierce competition, many strategies must be prepared. Competitive strategy is able to affect the overall performance of the corporation in order to win the competition. The purpose of this research is to prove the outcome of Competitive Differentiation Strategy, Cost Leadership Strategy and Focus Strategy on Corporation Performance either simultaneously or partially. This research was conducted on sub-division corporation retail listed on the Indonesia Stock Exchange for the 2017-2019 period. The quantitative research used as methodology in this research, using 21 research samples over a period of three years so that 63 samples are obtained. The results showed that Differentiation, Cost Leadership, and Focus simultaneously had a significant out come on NPM. Partially, differentiation has a positive outcome on NPM, while Cost Leadership and Focus have no significant out come on NPM.